Biosynthesis of Oligomeric Anthocyanins from Grape Skin Extracts - Hwang, Jin-Woo (Molecules, 2017)
We synthesized oligomeric anthocyanins from grape skin-derived monomeric anthocyanins such as anthocyanidin and proanthocyanidin by a fermentation technique using Aspergillus niger, crude enzymes and glucosidase. The biosyntheses of the oligomeric anthocyanins carried out by the conventional method using Aspergillus niger and crude enzymes were confirmed by ESI-MS. The molecular weight of the synthesized anthocyanin oligomers was determined using MALDI-MS. The yield of anthocyanin oligomers using crude enzymes was higher than that of the synthesis using Aspergillus fermentation. Several studies have been demonstrated that oligomeric anthocyanins have higher antioxidant activity than monomeric anthocyanins. Fermentation-based synthesis of oligomeric anthocyanins is an alternative way of producing useful anthocyanins that could support the food industry.